ANALISIS PENGARUH MEKANISME PENGAWASAN STAKEHOLDERS TERHADAP TINDAKAN AGRESIVITAS PAJAK (Studi empiris pada perusahaan yang terdaftar di Bursa Efek Indonesia (BEI) dengan periode pengamatan tahun 20 - Mayveni (AKT 16 UMY 050, 2016)
mechanism consisting of: frequency of board meetings, the competence of the audit committee, the audit committee meeting frequency, managerial ownership, and litigation against the aggressive actions of tax measured by effective cash tax rate (CETR). The population of this research are companies listed on the Indonesia stock exchange (BEI) in 2014. this research Sample was selected using a purposive sampling method. Based on the method of purposive sampling, there were 103 companies that meet the criteria. The research of using multiple linear regression analysis The results showed that the frequency of audit committee meetings have a significant positive effect on the aggressiveness of tax measures and managerial ownership has a negative and significant impact on the aggressiveness of the tax measures. Whereas the other variables did not significantly influence the aggressiveness of tax measures. Keywords: stakeholder’s oversight, the frequency of board meetings, the competence of the audit committee, the audit committee meeting frequency, managerial ownership, litigation, tax aggressiveness